Kebaktian Pembaharuan Janji Baptis: Sebuah Perwujudan Integrasi Ibadah dan Penggembalaan - Budianto Lim (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2023)
Abstract. This article discusses the importance of the worship service for renewing the baptismal promise. Such renewal can be seen as a way of integrating worship and pastoral ministry for the strengthening of Christian identity. Christian identity marked by baptism has been viewed as a formality and God’s people become a spectator. The promise made in baptism as an important milestone of discipleship has slowly lost its influence because many forget it. Thus, the church needs to guide the people into the process of renewing such a promise. This study was conducted by literature research methods to analyze the biblical-theological meaning of Jesus' baptism in Matthew 3:13-17. The results of this study showed that baptismal vows need to be renewed continuously and facilitated through the holding of religious services. The service of renewing baptismal promises is not a re-baptization but the maintenance of the meaning and power of the baptism that has been received.Abstrak. Artikel ini membahas pentingnya kebaktian pembaharuan janji baptis sebagai wujud integratif antara ibadah dan penggembalaan demi penguatan identitas Kristiani. Identitas yang ditandai melalui ritual baptisan seringkali dipandang sebatas formalitas dan diikuti sebagai tontonan bagi umat yang sudah dibaptis. Janji baptis sebagai tonggak awal kemuridan menjadi kurang berpengaruh dalam perjalanan iman karena sudah dilupakan. Gereja perlu menuntun umat Allah ke dalam momen pembaharuan janji baptis dalam konteks kebaktian demi memelihara kesinambungan komitmen sebagai komunitas murid Kristus. Kajian ini menggunakan metode riset literatur untuk menganalisa makna biblis-teologis baptisan Yesus dalam Matius 3:13-17. Hasil kajian ini menunjukkan bahwa janji baptis perlu dibaharui secara kontinu dan difasilitasi lewat pelaksanaan kebaktian. Kebaktian pembaharuan janji baptisan bukanlah pembatisan ulang namun pemeliharan makna dan kekuatan baptisan yang telah diterima.